A Exploring Bangladeshi Minority Students’ Attitudes towards English: A Quantitative Study on the Munda of the Sundarbans Regions - Siddique, Saifullah; Haque, Md. Samyul ((JELE) Journal Of English Language and Education, 2024)
Evaluating the Munda students, a minority community in Bangladesh living in the Sundarbans region, regarding the English language is a significant area of interest in educational research. The objective of this study is to examine the attitudes of students towards English, the determinants of these attitudes, the encountered difficulties, and the consequences on academic achievements. The primary results suggest that the Munda students hold favourable evaluations of English and there are no significant differences in motivation between genders and within classes on the importance of English for higher education and careers. Furthermore, there is no apparent correlation between the duration of time devoted to studying English and the level of proficiency attained. This research underscores the need to enact educational policies and distribute resources to support minority students. This study offers valuable insights for policymakers and educators aiming to enhance English language education among minority communities in Bangladesh.